PENGARUH TAMBAHAN PERBAIKAN PENGHASILAN DAN EFEKTIVITAS KERJA TERHADAP KINERJA APARATUR SIPIL NEGARA DI LINGKUNGAN PEMERINTAH DAERAH KABUPATEN KOLAKA TIMUR - Suute, Aspian; Mas’ud, Arifuddin; Yunus, Asraf (JIAR : Journal Of International Accounting Research, 2024)
This study aims to determine and analyze the influence of additional income improvement and work effectiveness on the performance of Civil Servants in the Local Government of East Kolaka Regency. The sample in this study consists of a portion of Civil Servants in the Local Government of East Kolaka Regency, totaling 97 individuals. This study uses multiple linear regression analysis. The results of the study show that: (1) Additional income improvement and work effectiveness have a positive and significant effect on the performance of Civil Servants in the Local Government of East Kolaka Regency. (2) Additional income improvement has a positive and significant effect on the performance of Civil Servants in the Local Government of East Kolaka Regency. (3) Work effectiveness has a positive and significant effect on the performance of Civil Servants in the Local Government of East Kolaka Regency.